Business writing for dummies - Canavor, Natalie 1942- (John Wiley & Sons, 2017)
Business writing that gets results The ability to write well is a key part of your professional success. From reports and presentations to emails and Facebook posts, whether you're a marketer, customer service rep, or manager, being able to write clearly and for the right audience is critical to moving your business forward. The techniques covered in this new edition of Business Writing For Dummies will arm you with the skills you need to write better business communications that inform, persuade, and win business. How many pieces of paper land on your desk each day, or emails in your inbox? Your readers?the people you communicate with at work?are no different. So how can you make your communications stand out and get the job done? From crafting a short and sweet email to bidding for a crucial project, Business Writing For Dummies gives you everything you need to achieve high-impact business writing. Draft reports, proposals, emails, blog posts, and more Employ editing techniques to help you craft the perfect messages Adapt your writing style for digital media Advance your career with great writing In today's competitive job market, being able to write well is a skill you can't afford to be without?and Business Writing For Dummies makes it easy!
Includes index. - Online resource; title from PDF title page (EBSCO, viewed April 12, 2017)
Keywords: Business writing; Business communication; Style commercial; Communication dans l'entreprise; LANGUAGE ARTS & DISCIPLINES; Composition & Creative Writing; LANGUAGE ARTS & DISCIPLINES; Rhetoric; REFERENCE; Writing Skills